Biochemical Characterization of a Haloalkane Dehalogenase DadB from Alcanivorax dieselolei B-5 - Li, Anzhang; Shao, Zongze (PloS one, 2014)
Recently, we found that Alcanivorax bacteria from various marine environments were capable of degrading halogenated alkanes. Genome sequencing of A. dieselolei B-5 revealed two putative haloalkane dehalogenase (HLD) genes, which were supposed to be involved in degradation of halogenated compounds. In this report, we confirm for the first time that the Alcanivorax bacterium encodes a truly functional HLD named DadB. An activity assay with 46 halogenated substrates indicated that DadB possesses broad substrate range and has the highest overall activity among the identified HLDs. DadB prefers brominated substrates; chlorinated alkenes; and the C2-C3 substrates, including the persistent pollutants of 1,2-dichloroethane, 1,2-dichloropropane and 1,2,3-trichloropropane. As DadB displays no detectable activity toward long-chain haloalkanes such as 1-chlorohexadecane and 1-chlorooctadecane, the degradation of them in A. dieselolei B-5 might be attributed to other enzymes. Kinetic constants were determined with 6 substrates. DadB has highest affinity and largest k cat/K m value toward 1,3-dibromopropane (K(m) = 0.82 mM, k(cat)/K(m) = 16.43 mM(-1) · s(-1)). DadB aggregates fast in the buffers with pH ≤ 7.0, while keeps stable in monomer form when pH ≥ 7.5. According to homology modeling, DadB has an open active cavity with a large access tunnel, which is supposed important for larger molecules as opposed to C2-C3 substrates. Combined with the results for other HLDs, we deduce that residue I247 plays an important role in substrate selection. These results suggest that DadB and its host, A. dieselolei B-5, are of potential use for biocatalysis and bioremediation applications.